2009
DOI: 10.1093/humrep/dep113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of GnRH and gonadotrophic hormone receptors affect the phenotype of polycystic ovary syndrome

Abstract: Genetic variants of the HPG-axis were associated with a modest but significant effect on the phenotype of PCOS. FSHR variants were strongly associated with the severity of clinical features of PCOS, such as levels of gonadotrophic hormones and the presence of hyperandrogenism, but not disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 33 publications
9
82
2
Order By: Relevance
“…In our study, rs13405728 was not associated with PCOS among Bahraini Arab subjects, which was in agreement with recent studies on Dutch [19], and USA women of European ancestry [18,20], but in sharp contrast to two independent Chinese studies, which confirmed its strong association with PCOS in Chinese [6] and in Han Chinese [17] subjects. In addition to rs13405728, rs2293275 was not associated with PCOS among Bahraini Arab (this study) and Dutch [25] subjects, with comparable case:control MAF recorded for Bahraini Arab (0.34:0.34) and Dutch (0.40:0.42) cases and controls.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In our study, rs13405728 was not associated with PCOS among Bahraini Arab subjects, which was in agreement with recent studies on Dutch [19], and USA women of European ancestry [18,20], but in sharp contrast to two independent Chinese studies, which confirmed its strong association with PCOS in Chinese [6] and in Han Chinese [17] subjects. In addition to rs13405728, rs2293275 was not associated with PCOS among Bahraini Arab (this study) and Dutch [25] subjects, with comparable case:control MAF recorded for Bahraini Arab (0.34:0.34) and Dutch (0.40:0.42) cases and controls.…”
Section: Discussionsupporting
confidence: 66%
“…We analyzed the association of PCOS with 11 SNPs from LHCGR and FSHR previously tested for their association with PCOS in European [18][19][20]25], and non-European [17,[26][27][28][29] populations. This case-control sample included 203 women with PCOS and 211 age-and ethnically-matched (Bahraini Arab) control women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant association between the polymorphism Ala307Thr and PCOS was also reported by a recent study on Chinese women [11]. In contrast, the existence of significant differences in the allele distribution of FSH-R polymorphysm 307 in women with PCOS was not confirmed among Turkish adolescent girls [12], and on women of Caucasian origin [13]. We studied herein an homogeneous population of women with "full" PCOS and a control population of IVF patients with normal ovary.…”
Section: Discussionmentioning
confidence: 61%
“…A couple of studies have been published, one showing that normo-ovulatory women with homozygous Ala307 have the best responsiveness to exogenous FSH [8], the other showing no 307 variant-linked changes in the responsiveness to FSH in chronic anovulatory subjects [9]. A significant increase in the Ala307Thr genotype frequency among women with PCOS was also reported [9][10][11], but not confirmed by other studies [12,13].…”
Section: Introductionmentioning
confidence: 93%